Creating illusion in computer aided performance - Marshall, Joe (2009)
This thesis studies the creation of illusion in computer aided performance. Illusion is created here by using deceptions, and a design framework is presented which suggests several different deception strategies which may be useful. The framework has been developed in an iterative process in tandem with the development of 3 real world performances which were used to explore deception strategies.